2021
DOI: 10.1007/s42452-021-04419-5
|View full text |Cite
|
Sign up to set email alerts
|

Bench-scale assessment of three copper-based algaecide products for cyanobacteria management in source water

Abstract: Three copper-based algaecide products were investigated for use in a drinking water source to address cyanobacteria growth. Bench-scale experiments were used to determine the optimal dose of each product given Lake Rockwell’s indigenous population and reservoir-specific characteristics. The optimal dose of Cutrine Ultra was determined to be a quarter dose (corresponding to 0.125 mg/L Cu) as it decreased 55% of the cyanobacteria population with limited release of microcystin and minimal rebound in the cyanobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Chemical control entails the application of compounds that are harmful to toxic cyanobacteria [36]. Artificial compounds such as commercial copper salt solutions [37,38] are often used, but natural compounds such as methanolic allelochemicals of seaweed are also available [39]. The modes of action of these chemical control agents can be direct or indirect.…”
Section: Control Methodsmentioning
confidence: 99%
“…Chemical control entails the application of compounds that are harmful to toxic cyanobacteria [36]. Artificial compounds such as commercial copper salt solutions [37,38] are often used, but natural compounds such as methanolic allelochemicals of seaweed are also available [39]. The modes of action of these chemical control agents can be direct or indirect.…”
Section: Control Methodsmentioning
confidence: 99%
“…Capping agents, such as lanthanum-activated modified clay and alum, can prevent sedimentary phosphorus from leaching into water; however, these agents may produce water quality issues and the associated ecological risks are poorly understood [ 14 ]. Dosing waterbodies with nutrient sequestering chemicals presents an additional option for active source water control [ 15 ]. Kibuye et al found that among surveyed utilities, algaecide addition and aeration were the two most frequently deployed source water management strategies [ 2 ].…”
Section: Introductionmentioning
confidence: 99%